A study of sequence and function divergence of pilz proteins - Cheang, Qing Wei (2018)
Cyclic di-GMP is a near-ubiquitous second messenger that mediates important cellular functions in many species of bacteria. Cyclic di-GMP binds to a diverse range of proteins receptors/effectors. The PilZ protein family is one of the largest families of specialized cyclic di-GMP receptors. Currently more than 26, 000 PilZ proteins are recorded in the InterPro database and most these proteins have unknown function. In this research project, I performed a large-scale analysis of single and di-domain PilZ proteins using the sequence similarity networking (SSN) tool and then analysed the largest clusters in detail; and generated sequence logos to unveil highly conserved residues that may be important for the function of the PilZ proteins. One of the most important observations is that PilZ proteins exhibit enormous sequence divergence and share little in conservation amongst different clusters, which suggest that PilZ proteins are likely to have different cellular functions. In addition of the large-scale bioinformatic analysis, I also performed biochemical and genetic experiments to probe the biological function of four uncharacterized PilZ proteins (PA0012, PA4324, PA2989 and PA3353) from the opportunistic pathogen P. aeruginosa PAO1. By transcriptome analysis, I found that the single domain PilZ protein PA0012 specifically suppresses genes of the anti-bacterial HSI-I gene cluster. This observation is in accordance with bacterial competition assays which showed that the ΔPA0012 strains displayed enhanced killing of the prey bacteria whereas the PA0012 overexpression strain displayed reduced killing of prey bacteria. Meanwhile, the second single-domain PilZ protein PA4324 was found to regulate the expression of the pqs operon and other genes under the control of the PQS signalling network. I discovered that the di-domain PilZ protein PA2989 likely plays a protective role because many genes that play protective roles were down-regulated when PA2989 was deleted. Furthermore, I found that PA2989 likely represents a unique class of di-domain PilZ proteins that contain an inserted α-helical domain between the two cyclic di-GMP-binding motifs. For the second di-domain protein PA3353, we found that the protein is involved in the regulation of flagellar motor output by using cell-tethering assay and swimming speed analysis. Based on the observations, I have proposed a model where PA3353 (also known as FlgZ) mediates flagellar motor torque and speed output by interacting with flagellar stator proteins. Collectively, the bioinformatical and experimental work described in this thesis bring us one step closer towards understanding the functional diversity of the entire PilZ protein superfamily and elucidating the functions of PilZ proteins in the model organism P. aeruginosa PAO1.